2017
DOI: 10.1519/jsc.0000000000001583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Volume, High-Intensity Training on Performance in Competitive Swimmers: A Systematic Review

Abstract: Nugent, FJ, Comyns, TM, Burrows, E, and Warrington, GD. Effects of low-volume, high-intensity training on performance in competitive swimmers: a systematic review. J Strength Cond Res 31(3): 837-847, 2017-The purpose of this systematic review was to examine the extent and quality of the current research literature to determine the effects of low-volume, high-intensity training (HIT) on physiological performance and swimming performance in competitive swimmers. The methodology followed the preferred reporting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 50 publications
3
44
3
2
Order By: Relevance
“…A recent systematic review by Nugent et al (2016) found only 2 studies involving quality or HIT interventions in youth swimmers. The studies involved a 40 – 50% reduction in training volume for duration of 4 – 5 weeks and resulted in significant improvements in physiological performance (V02max, sub-maximal lactate indices and peak lactate indices) as well as swimming performance (Faude et al, 2008; Sperlich et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review by Nugent et al (2016) found only 2 studies involving quality or HIT interventions in youth swimmers. The studies involved a 40 – 50% reduction in training volume for duration of 4 – 5 weeks and resulted in significant improvements in physiological performance (V02max, sub-maximal lactate indices and peak lactate indices) as well as swimming performance (Faude et al, 2008; Sperlich et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review by Nugent et al (2016) identified 4 HIT studies that were conducted on senior swimmers (Houston et al, 1981; Kame et al, 1990; Kilen et al, 2014; Termin and Pendergast, 2000). The studies ranged in duration from 6.5 weeks to 4 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of published literature to support USRPT has been previously highlighted by numerous critics. 20,48,49 A large amount of USRPT literature was found on the Swimming Science Journal, the personal website of Professor Brent Rushall; however, this literature was nonpeer reviewed, largely anecdotal and heavily biased. The use of peers to assess the work of fellow scientists has been a foundation of the publication process for at least 200 years.…”
Section: The Concerns Surrounding Usrpt a Lack Of Peer-reviewed Publimentioning
confidence: 99%
“…[15][16][17] However, USRPT has resulted in a large amount of controversy in the swimming community. [18][19][20][21][22][23][24] The training methodologies of elite swimming coaches typically involve prescribing a high-volume, low-intensity training (HVT) program which is defined as a training program that focuses on performing low-intensity training (<2 mM blood lactate) of longer duration, 25 also referred to as a "traditional or yardage program". 26 Training volumes of around 40 km or 16 hrs per week are common in competitive swimmers, even among youth cohorts.…”
mentioning
confidence: 99%